GONAD MATURATION OF TWO INTERTIDAL BLOOD CLAMS Anadara granosa (L.) AND Anadara antiquata (L.) (BIVALVIA: ARCIDAE) IN CENTRAL JAVA - Norma Afiati (JOURNAL OF COASTAL DEVELOPMENT, 2007)
The reproductive cycles of male and female Anadara granosa and Anadara antiquata which have been studied and compared by histological techniques showed great anatomical similarity. Gametogenesis is associated with a system of follicle cells which break down as the gametes approach maturity. The arrangement of follicle cells is characteristics of the sex. In the female, gametogonia are peripheral to the follicle cells, whilst in the male they are interstitial. The process of spermatogenesis parallel the classical vertebrate pattern, i.e. successive layers of spermatogenic cells (spermatogonia, primary and secondary spermatocytes, spermatids, and spermatozoa) occurring more or less regularly in succession toward the centre of the follicle. The diameter of the maximum size oocytes is 75mm for A. granosa and 65mm for A. antiquata. Spawning in both A. granosa and A. antiquata is progressing gradually throughout the year as indicated by the availability of various stages of oogonia and spermatogonia; for which the highest number of oogonia were those of 25-40mm diameter. The histological study indicated that both species are iteroparous with planktotrophic type of development, yet performing a short period of pelagic life (ca 1 month).